Agro‐morphological and nutritional assessment of chenopod and quinoa germplasm—Highly adaptable potential crops - Bhardwaj, Rakesh; Yadav, Rashmi; Vishwakarma, Harinder; Sharma, Kriti; Chandora, Rahul; Rana, Jai Chand; Riar, Amritbir (Wiley, 2023)
Quinoa belongs to the family Chenopodiaceae , a pseudo‐grain having high nutritional value and is considered an underexploited vegetable crop with the potential to improve the nutritional security of millions. Therefore, assessing genetic diversity in Chenopodium germplasm to untap nutritional and site‐specific adaptation potential would be of prime importance for breeders/researchers. The present study used 10 accessions of two Chenopodium species, that is, C. quinoa and C. album . Quantitative and qualitative phenotypic traits, proximate composition, minerals, and amino acids profiles were studied to compare the differences in nutritional value and extent of genetic diversity between these two species. Our results showed significant variation existed in yield attributing agro‐morphological traits. All the traits were considered for hierarchical clustering and principal components analysis. Large genetic variability was observed in traits of Chenopodium accessions. The protein, dietary fiber, oil, and sugar content ranged from 16.6% to 19.7%, 16.8% to 26%, 3.54% to 8.46%, and 3.74% to 5.64%, respectively. The results showed that C. album and C. quinoa seeds had good nutritional value and health‐promoting benefits. The C. quinoa was slightly ahead of than C. album in terms of nutritional value, but C. album accession IC415477 was at par for higher test weight, seed yield (117.02 g/plant), and other nutritional parameters with C. quinoa accessions. IC415477 and other potential accessions observed in this study may be taken up by breeders/researchers in the near future to dissect nutritional value of Chenopodium and related species for dietary diversity, which is imperative for the nutritional security of the ever‐growing world's population.